PENGARUH PERSEPSI HARGA, KUALITAS LAYANAN DAN CITRA MEREK TERHADAP KEPUASAN PELANGGAN DAN DAMPAKNYA TERHADAP LOYALITAS PELANGGAN TAKSI NEW ATLAS DI KOTA SEMARANG - Nastiti, Aridara; Astuti, Sri Rahayu Tri (Faculty of Economics and Business Diponegoro University, 2019)
This study aims to analyze the influence of each variable of Price Perception, Service Quality and Brand Image on Customer Satisfaction and Its Impact on Customer Loyalty of New Atlas Taxi Customers in Semarang City.The population in this study were customer of Semarang New Atlas Taxi. The sample in this study is accounted for 100 respondents, determined by using purposive sampling with the criteria: adults whom > 17 years old and had already used the New Atlas Taxi service. Data analysis method included descriptive statistics, instruments test, models test and hypothesis test. Instruments test conducted by validity and reliability test. The model test used is the F (Goodness of Fit) Test and the Adjusted R2 test (coefficient of determination). Furthermore, the hypothesis testing in this study uses regression analysis by t test with standard beta coefficient and significancy level <0.05.Based on the results of the hypothesis test concluded that: 1. Price perception has a positive and significant effect on customer satisfaction. 2. Service quality has a positive and significant effect on customer satisfaction. 3. Brand image has a positive and significant effect on customer satisfaction. 4. Customer satisfaction has a positive and significant effect on customer loyalty